Konsep Wasathiyah dalam Perspektif Hadis Tarbawi - Zahratul Hayyah; Febry Yaningsih; Aulia Fitri; Dwi Meutia Hasni (STIKes Ibnu Sina Ajibarang, 2026)
The discourse on wasathiyah has become increasingly important in contemporary Islamic education due to the emergence of religious extremism, intolerance, and imbalanced understandings of Islamic teachings. However, many studies on wasathiyah primarily focus on Qur’anic perspectives, while discussions that specifically examine the concept through the lens of hadith tarbawi and its educational implications remain relatively limited. This study aims to analyze the concept of wasathiyah from the perspective of hadith tarbawi and to identify the educational values embedded within it as a foundation for character formation in Islamic education. This research employs a qualitative approach using the library research method. Data were collected from relevant prophetic traditions, Qur’anic verses, and supporting scholarly literature, and were analyzed through content analysis techniques. The findings reveal that the concept of wasathiyah in hadith tarbawi is manifested through three fundamental educational values: the prohibition of excessiveness (an-nahy ‘an al-ghuluw), tolerance (as-samahah), and balance (at-tawazun). These values promote a balanced relationship between spiritual and physical needs, individual and social responsibilities, as well as worldly and hereafter-oriented goals. This study contributes to the development of Islamic educational thought by providing a hadith-based conceptual framework of wasathiyah that can serve as a foundation for cultivating moderate, adaptive, and morally grounded learners in contemporary society.